Medicare and the Rise of American Medical Patenting: The Economics of User-Driven Innovation - Jeffrey P. Clemens; Morten Olsen (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Innovation is part idea generation and part development. We build a model of “innovating-by-doing,” whereby ideas come to practitioners. Successful innovation requires that practitioners' ideas be developed through costly effort. Our model nests existing theories of laboratory research and learning-by-doing. Empirically, we analyze the effect of the U.S. Medicare program on medical equipment innovation. Our model's structure allows us to infer the Medicare program's aggregate effects. We estimate that Medicare's introduction led to a 20 to 30 percent increase in medical equipment patenting across the United States, of which roughly half is due to the innovating-by-doing channel.
Keywords: I13; O38; O31; H51; 330; innovation and invention; medical innovation; health care; health insurance